2019
DOI: 10.1021/acsomega.9b02570
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Head Pectin with Different Molecular Weights as Promising Green Corrosion Inhibitors of Carbon Steel in Hydrochloric Acid Solution

Abstract: Three sunflower head pectin (SFHP) with different molecular weights (Mw = 4.50, 97.23, and 254.64 kDa) were obtained by enzyme-assisted extraction and characterized by FTIR and 1H NMR spectroscopy. The corrosion inhibition of mild steel in 1 M HCl solution was evaluated by the weight loss measurement. The inhibition efficiency (IE%) increased as its concentration increases and decreased as the temperature increases. The SFHP with the lowest Mw of 4.50 kDa exhibited an IEmax of 92.05% at the medium concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The nature of the adsorption process may be physical, chemical, or a mixture of the two-mentioned adsorption types. 36 The evaluated thermodynamic and kinetic parameters in the present study supported that the nature of adsorption of the two examined inhibitors on the steel surface in H 2 SO 4 solution was mainly physical. Adsorption of the inhibitor molecules on the steel surface was set to depend on their chemical structures, intensity of surface charge, potential of zero charge (PZC) of metal, and the composition of the corrosive environment.…”
Section: ■ Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The nature of the adsorption process may be physical, chemical, or a mixture of the two-mentioned adsorption types. 36 The evaluated thermodynamic and kinetic parameters in the present study supported that the nature of adsorption of the two examined inhibitors on the steel surface in H 2 SO 4 solution was mainly physical. Adsorption of the inhibitor molecules on the steel surface was set to depend on their chemical structures, intensity of surface charge, potential of zero charge (PZC) of metal, and the composition of the corrosive environment.…”
Section: ■ Introductionsupporting
confidence: 75%
“…The evaluated values of E a * (Table 5) in the presence of the inhibitors were found to be higher than those obtained in the corrosive solution verifying adsorption of the tested molecules on the mild steel surface and constructing a barrier between the steel surface and the corrosive medium. 36 Furthermore, the range of E a * values (5.86−20.78 kJ mol −1 ) is lower than 80 kJ mol −1 confirming the physical adsorption of the examined inhibitors. 41 These results are in good agreement with those based on the values of both ΔG o ads and ΔH o ads indicating the validity of the acquired investigational outcomes.…”
Section: ■ Introductionmentioning
confidence: 74%
“…The open-circuit potential (OCP) of the carbon steel electrode is a parameter that depends on the immersion time in the test solution. 38 Measurements were performed until the steady-state potentials were achieved, at which the equilibrium state occurs between the oxidation current ( i oxd ) and reduction current ( i red ). Figure 7 exhibits the variation of OCP ( E OCP ) as a function of the immersion time in the absence and presence of CT-Cu inhibitor at different doses in the WBM at 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that R ct values increase significantly in the presence of [1,8-Nap]­[CETSA], while the C dl value decrease is probably attributed to the replacement of water and HCl molecules with large dielectric constants of [1,8-Nap]­[CETSA] molecules; these results illustrate that a protective layer formed on the metal surface to inhibit the corrosion process. Meanwhile, the EIS measurement showed that η was over 90%, and inhibitor molecules can be stably adsorbed on the surface of Q235 steel.…”
Section: Application Of 18-naphthyridinesmentioning
confidence: 98%